PEMASARAN PARIWISATA MELALUI STRATEGI PROMOSI OBJEK WISATA ALAM, SENI DAN BUDAYA (Studi Kasus di Pulau Rote NTT) - Manafe, Janri.D; Setyorini, Tuty; Alang, Yermias A. (BISNIS, 2016)
Development of tourism in Indonesia is in line with the government program to promote tourism as an addition to foreign exchange outside the non-oil sector. One area in Indonesia which has a variety of tourist attractions that the island of Rote. Natural attractions on the island of Rote has many interesting panorama, as a unique tourist attraction. Promotion strategies can be used as a tool to market their tourism products in the form of natural attractions, arts and culture are an excellent product and all the tourism potential that is in place. The research objectives: 1) To describe the profile of nature, art and culture of the island of Rote, 2) To determine the model Rote Island tourism marketing throughpromotional strategies of natural attractions, art and culture. The method used in this study is a qualitative method using a case study approach regarding the promotion strategies of natural attractions, art and culture of the island of Rote. The research used the ethnographic approach. Ethnography is an empirical and theoretical approaches that aim to get a description and a thorough analysis of culture based on field research (fieldwork) intensive. Sources of information in this study consisted of four people, namely, Head of Promotion, Head Attractions, Head of Culture and Head of Bina Sarana. The technique of collecting data using interviews, observation and documentation. The data were analyzed by using domain analysis. Technique authenticity of data using triangulation sources that checks the accuracy of data on the interview and documentation. The strategy undertaken by the Department of Culture and Tourism Rote Ndao is the author of view is verysimple so it does not boost the number of domestic and international tourists who proved in the tables of foreign tourists and Vishnu, who in turn have an impact on revenue receipts for the tourism sector is very small. Therefore essential drawn up a proper marketing strategy, effective and efficient. Tourism Marketing Model Rote- island of Nusa Tenggara Timur Through Promotion Strategy Object Nature Tourism, Arts and Culture Visit To Boost Domestic and International right is through a strategy Promotion Mix (Kotler). Promotion strategy defined Mix 5 (five) are: Advertising (advertising), Sales Promotion (Sales Promotion), Public Relations (PR), the Personal Sales (Personal Selling) and a Direct Marketing (DirectMarketing).